Effect of Grain Size and Incidence Angle on Erosive Wear of Polyurea Coating - Justyna Sokolska; Piotr Sokolski (Applied Sciences, 2025)
This study investigated the erosive wear of a polyurea coating with a hardness of 95 ShA and a thickness of 3 mm applied to a 3 mm thick plate made of S235 steel. The process of erosive wear was carried out using a stream of compressed air containing abrasive grains of aluminum oxide (Al2O3). The erosive wear was studied using different incidence angles (45°, 60° and 90°) and erosive grain sizes. Thus, the effects of the incidence angle and erosive grain size on the erosive wear of the polyurea coating were analyzed. Erosive wear was determined as linear wear: the depth of the wear trace was measured using an optical profilometer. This study showed a non-linear correlation between erosive wear, incidence angle and erosive particle size. In addition, a qualitative study of the surface of the coating after a wear test was carried out using a scanning electron microscope, which made it possible to describe the mechanisms of erosive wear of the polyurea coating.